Electrolyte and lithium ion battery

By adding compounds A and B to the electrolyte of lithium-ion batteries, the acid-generating reaction and HF production of lithium hexafluorophosphate are hindered, and the problems of acid value growth and SEI interface decomposition in the later stages of the battery cycle are solved, forming a sulfur- and phosphorus-containing composite interface, which improves lithium High and low temperature performance of ion batteries.

CN119315115AActive Publication Date: 2025-01-14HEFEI SMOOTHWAY ELECTRONIC MATERIALS CO LTD +2
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411491562.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-14
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

Under the conditions of recycling and high-temperature storage, the dissolution of metal ions leads to a significant decline in battery performance, especially the lithium hexafluorophosphate in the electrolyte decomposes during charging and discharging to produce free hydrofluoric acid, resulting in an increase in the acid value of the electrolyte. High, destroys the stability of the SEI layer.

Method used

An electrolyte is used that contains compound A and compound B. Compound A can hinder the forward reaction of acid production by lithium hexafluorophosphate. Compound B reacts with lithium hexafluorophosphate at high voltage and high temperature to produce HF, forming a synergistic effect and significantly easing the acid value loss in the later stages of the battery cycle. growth, inhibiting the decomposition of the SEI interface and forming a sulfur- and phosphorus-containing composite interface, improving the low-temperature transmission characteristics of lithium ions and the high-temperature stability of the electrolyte.

Benefits of technology

By significantly mitigating the growth of the acid value in the later stages of the battery cycle and inhibiting the decomposition of the SEI interface, it forms excellent lithium ion transport characteristics and high temperature stability, and improves the high and low temperature performance of lithium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315115A_ABST
    Figure CN119315115A_ABST
Patent Text Reader

Abstract

The invention discloses an electrolyte and a lithium ion battery, the electrolyte comprises a lithium salt, a non-aqueous organic solvent and an additive, the lithium salt comprises lithium hexafluorophosphate, the additive comprises a compound A shown as a structural formula 1 and a compound B shown as a structural formula II, # imgabs0 #, and R1-R4 are respectively and independently selected from hydrogen, alkyl, alkenyl and alkynyl; and R5-R6 are respectively and independently selected from halogen, alkyl and halogen substituted alkyl. The compound A and the compound B in the electrolyte can generate a synergistic effect, so that the increase of an acid value in the later period of battery circulation is remarkably relieved, and the decomposition of an SEI interface is effectively inhibited; and a sulfur and phosphorus-containing composite interface can also be formed, and the low-temperature transmission characteristic of lithium ions and the high-temperature stability of the electrolyte are improved, so that the electrolyte disclosed by the invention can enable the lithium ion battery to have relatively good high and low temperature performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an electrolyte and a lithium ion battery. Background Art

[0002] In recent years, new energy vehicles have become one of my country's strategic emerging industries, and high-performance lithium battery technology is the key to achieving the national new energy vehicle strategy. The performance of lithium-ion batteries will be affected by the oxidation and decomposition of the electrolyte, especially under the conditions of cyclic use and high-temperature storage, the dissolution of metal ions will further cause a significant decrease in battery performance. However, with the growth of market demand for lithium-ion batteries, the requirements for their comprehensive performance are also constantly increasing.

[0003] In order to improve the overall performance of lithium-ion batteries, the use of specific additives is an effective strategy. For example, studies have shown that the use of sulfate compounds as negative electrode film-forming agents can improve the electrochemical properties of batteries. However, these compounds will react with lithium hexafluorophosphate in the electrolyte under high voltage and high temperature conditions to generate harmful hydrofluoric acid (HF); in addition, lithium hexafluorophosphate in the electrolyte will gradually decompose during the charge and discharge cycle of lithium-ion batteries to produce free hydrofluoric acid. As the concentration of hydrofluoric acid in the electrolyte increases, the acid value of the electrolyte also increases, which will cause changes in the properties of the electrolyte and destroy the stability of the SEI layer that has been formed; once the SEI layer is damaged, it may lead to a decrease in battery performance, such as accelerated capacity decay, increased impedance, and shortened cycle life.

[0004] Therefore, there is an urgent need for an electrolyte and a lithium ion battery to solve the deficiencies of the existing technical problems. Summary of the invention

[0005] In view of the above problems, the object of the present invention is to provide an electrolyte and a lithium ion battery, wherein compound A and compound B in the electrolyte can produce a synergistic effect, significantly alleviate the increase of the acid value in the later stage of the battery cycle, and effectively inhibit the decomposition of the SEI interface; they can also form a sulfur- and phosphorus-containing composite interface, improve the low-temperature transmission characteristics of lithium ions and the high-temperature stability of the electrolyte, so that the electrolyte of the present invention can make the lithium ion battery have better high and low temperature performance.

[0006] To achieve the above objectives, the present invention provides an electrolyte in a first aspect, comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the lithium salt comprises lithium hexafluorophosphate, and the additive comprises a compound A represented by structural formula 1 and a compound B represented by structural formula II.

[0007]

[0008] Where R 1 ~R 4 are each independently selected from hydrogen, alkyl, alkenyl, alkynyl; R5 ~R 6 Each is independently selected from halogen, alkyl, and halogen-substituted alkyl.

[0009] Compared with the prior art, the electrolyte of the present invention includes compound A shown in structural formula 1 and compound B shown in structural formula II, wherein compound B reacts with lithium hexafluorophosphate at high voltage and high temperature to produce HF, destroying the stability of the battery interface and causing the battery performance to deteriorate, while compound A can hinder the forward reaction of lithium hexafluorophosphate to produce acid, and the chemical equilibrium moves toward the direction of lithium hexafluorophosphate, and the acid value of the electrolyte is greatly reduced, so compound A can significantly alleviate the increase of the acid value in the later stage of the battery cycle and effectively inhibit the decomposition of the SEI interface. In addition, compound A and compound B can form a composite interface layer at the interface of the electrode electrolyte, and the composite interface layer has better lithium ion transmission characteristics, is not easy to shrink holes at low temperatures, can maintain the lithium ion transmission channel at low temperatures, and improves the low temperature performance of the lithium ion battery; at the same time, the composite interface contains sulfur and phosphorus interfaces, so that the high temperature stability of the electrolyte is better. In summary, the compounds A and B of the present invention can produce a synergistic effect, significantly alleviate the increase of the acid value in the later stage of the battery cycle, and effectively inhibit the decomposition of the SEI interface; they can also form a sulfur- and phosphorus-containing composite interface, improve the low-temperature transmission characteristics of lithium ions and the high-temperature stability of the electrolyte, so the electrolyte of the present invention can make the lithium-ion battery have better high and low temperature performance.

[0010] Furthermore, R of the present invention 1 ~R 4 Each is independently selected from hydrogen, C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl; R 5 ~R 6 Each is independently selected from halogen, C1-C6 alkyl, halogen-substituted C1-C6 alkyl. Specifically, C1-C6 alkyl refers to a straight or branched saturated hydrocarbon group containing 1 to 6 carbon atoms, and these alkyl groups can be straight (normal) or branched (isomerized), such as but not limited to methyl, ethyl, n-propyl, isopropyl, n-butyl, tert-butyl, etc. Halogen can be fluorine (F), chlorine (Cl), bromine (Br), iodine (I). Halogen-substituted C1-C6 alkyl means that in a straight or branched alkane containing 1 to 6 carbon atoms, one or more hydrogen atoms are replaced by halogen atoms (fluorine F, chlorine Cl, bromine Br, iodine I); for example, halogen-substituted C1-C6 alkyl can be but not limited to monochloromethane, monofluoromethane, difluoroethane, trichloromethane, trifluoromethane or trifluoroethane.

[0011] Furthermore, the compound A of the present invention is at least one selected from the group consisting of compounds A1 to A3:

[0012]

[0013] Furthermore, the compound B of the present invention is selected from at least one of compounds B1 to B4:

[0014]

[0015] Further, the mass percentage of compound A of the present invention in the electrolyte is 0.1-5.0%; the mass percentage of compound B in the electrolyte is 0.1-10.0%. Specifically, the mass percentage of compound A in the electrolyte may be, but not limited to, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%; the mass percentage of compound B in the electrolyte may be, but not limited to, 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 9.8%, 10%. Preferably, the mass percentage of compound A of the present invention in the electrolyte is 0.1-2%; the mass percentage of compound B in the electrolyte is 0.1-5%.

[0016] Furthermore, the lithium salt of the present invention also includes lithium perchlorate (LiClO 4 ), lithium tetrafluoroborate (LiBF 4 ), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium methanesulfonate, lithium trifluoromethylsulfonate, lithium fluorosulfonate, lithium bis(oxalate)borate, lithium difluorooxalateborate, lithium difluorophosphate, lithium difluorobis(oxalate)phosphate, lithium bis(fluorosulfonyl)imide, lithium diphosphate and at least one of lithium lower aliphatic carboxylates. Specifically, the mass percentage of lithium salt in the electrolyte is 5 to 30%, such as the content of lithium salt may be but not limited to 5%, 10%, 15%, 20%, 25%, 30%; preferably, the mass percentage of lithium salt in the electrolyte is 5 to 18%.

[0017] Further, the non-aqueous organic solvent of the present invention is at least one of carbonate, carboxylic acid ester and ether compounds. Carbonate compounds have a higher dielectric constant (favorable for lithium salt dissociation) and good stability. Carboxylic acid ester compounds can provide a relatively high dielectric constant, help to improve the solubility of lithium salts in the electrolyte, and show good compatibility with certain positive electrode materials. Ether compounds have a lower viscosity and freezing point, that is, they can maintain good ion transport properties even at low temperatures.

[0018] Further, the carbonate compounds of the present invention include cyclic carbonates and chain carbonates. Specifically, the cyclic carbonates may be, but are not limited to, ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), pentylene carbonate, vinylene carbonate (VC) or their derivatives; chain carbonates include, but are not limited to, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and propylene carbonate.

[0019] Furthermore, the carboxylate compounds of the present invention include at least one of cyclic carboxylates and chain carboxylates. The cyclic carboxylates may specifically include but are not limited to at least one of γ-butyrolactone (GBL), γ-valerolactone (GVL), and δ-valerolactone (DVL); the chain carboxylates include but are not limited to methyl acetate (MAC), ethyl acetate (EA), propyl acetate (PA), butyl acetate (BA), propyl propionate (PP), and butyl propionate (BP).

[0020] Furthermore, the ether compounds of the present invention include cyclic ethers or chain ethers. The cyclic ethers may specifically include but are not limited to 1,3-dioxolane (DOL), 1,4-dioxolane (DX), crown ethers, tetrahydrofuran (THF), 2-methyltetrahydrofuran (2-CH 3 -THF), 2-trifluoromethyltetrahydrofuran (2-CF 3 -THF); the chain ether may specifically include but is not limited to dimethoxymethane, diethoxymethane, ethoxymethoxymethane, ethylene glycol di-n-propyl ether, ethylene glycol di-n-butyl ether, and diethylene glycol dimethyl ether.

[0021] Furthermore, the electrolyte of the present invention also includes an auxiliary agent, which is selected from vinylene carbonate (VC), vinylene carbonate (VEC), fluoroethylene carbonate (FEC), vinyl sulfite (ES), 1,3-propane sultone (PS), 1,3-propylene sultone (PES), 1,4-butane sultone (BS), vinyl sulfate (DTD), succinic anhydride (SA), maleic anhydride (MA), 2-methylmaleic anhydride (MMA), methyl carbonate-2-propynyl ester, tetravinylsilane, triallyl isocyanate, At least one of cyanurate, hexamethylene diisocyanate, o-phenanthroline, p-phenylene diisocyanate, 2,4-toluene diisocyanate, N-phenyl bis(trifluoromethanesulfonyl)imide, vinyl disulfate, phenyl methanesulfonate, vinyl disulfate, bis-spiro-propylene sulfate, hydroquinone difluorosulfonate, triallyl phosphate, tripropargyl phosphate, 2,4-butane sultone, methacrylate isocyanatoethyl, methane disulfonic acid methylene ester, tri(trimethylsilyl) borate, tri(trimethylsilyl) phosphate, tri(vinyldimethylsilyl) phosphate. Specifically, the mass percentage of the auxiliary agent of the present invention in the electrolyte is 0.1-5%, such as the auxiliary agent content can be but not limited to 0.1%, 0.5%, 1%, 1.6%, 1.9%, 2.6%, 3.2%, 3.8%, 4.3%, 4.8%, 5%. Preferably, the mass percentage of the auxiliary agent in the electrolyte is 0.1-2%.

[0022] Correspondingly, the second aspect of the present invention further provides a lithium-ion battery, comprising a positive electrode, a negative electrode, and the above-mentioned electrolyte.

[0023] Compared with the prior art, the compound A and compound B in the electrolyte of the present invention can produce a synergistic effect, significantly alleviate the increase of the acid value in the later stage of the battery cycle, and effectively inhibit the decomposition of the SEI interface; they can also form a sulfur-phosphorus composite interface, improve the low-temperature transmission characteristics of lithium ions and the high-temperature stability of the electrolyte, so the lithium-ion battery of the present invention has good high and low temperature performance.

[0024] Furthermore, the active material of the positive electrode of the present invention includes olivine-structured lithium-containing phosphates, lithium transition metal oxides and their respective modified compounds. Specifically, olivine-structured lithium-containing phosphates include but are not limited to lithium iron phosphate (such as LiFePO 4 ), composite materials of lithium iron phosphate and carbon, lithium manganese phosphate (such as LiMnPO 4 ), a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon. Lithium transition metal oxides include but are not limited to lithium cobalt oxide (such as LiCoO 2 ), lithium nickel oxide (such as LiNiO 2 ), lithium manganese oxide (such as LiMnO 2 、LiMn 2O 4 ), lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide (structure such as LiNi x Co y Mn 1-x-y M z O 2 , wherein 0.6≤x<0.9, x+y<1, 0≤z<0.08, M is at least one of Al, Mg, Zr and Ti). Preferably, the active material of the positive electrode of the present invention is LiNi 0.8 Co 0.1 Mn 0.1 Zr 0.03 O 2 .

[0025] Furthermore, the active material of the negative electrode of the present invention includes at least one of a carbon-based negative electrode, a silicon-based negative electrode, a tin-based negative electrode, and a lithium negative electrode. The carbon-based negative electrode may include graphite, hard carbon, soft carbon, graphene, mesophase carbon microspheres, etc.; the silicon-based negative electrode may include silicon materials, silicon oxides, silicon-carbon composite materials, and silicon alloy materials, etc.; the tin-based negative electrode may include tin, tin carbon, tin oxygen, and tin metal compounds; the lithium negative electrode may include metallic lithium or a lithium alloy, wherein the lithium alloy may specifically be at least one of a lithium silicon alloy, a lithium sodium alloy, a lithium potassium alloy, a lithium aluminum alloy, a lithium tin alloy, and a lithium indium alloy. DETAILED DESCRIPTION

[0026] In order to further illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific examples. It should be noted that, if specific conditions are not specified in the examples and comparative examples, they can be carried out according to conventional conditions or conditions recommended by the manufacturer, and if the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0027] Example 1

[0028] This embodiment provides a method for preparing a lithium ion battery, the steps comprising:

[0029] (1) The ternary material LiNi 0.8 Co 0.1 Mn 0.1 Zr 0.03 O 2 , conductive agent SuperP, adhesive PVDF and carbon nanotubes (CNT) are mixed evenly in a mass ratio of 96.5:1.5:1:1 to form a lithium-ion battery positive electrode slurry with a certain viscosity, which is coated on the aluminum foil for current collector, and the coating amount is 324g / m 2 , dried at 85°C and then cold pressed; then trimmed, cut into pieces, and slit, and then dried at 85°C for 4 hours under vacuum conditions, and the tabs were welded to make positive electrode sheets that meet the requirements;

[0030] (2) artificial graphite and silicon are mixed in a mass ratio of 90:10, and then mixed with a conductive agent SuperP, a thickener CMC, and an adhesive SBR (styrene-butadiene rubber latex) in a mass ratio of 95:1.5:1.0:2.5 to make a slurry, which is mixed evenly, and the mixed slurry is applied on both sides of a copper foil, and then dried and rolled to obtain a negative electrode sheet, thereby making a negative electrode sheet that meets the requirements;

[0031] (3) In a glove box filled with nitrogen (O 2 <1ppm,H 2 O<1ppm), ethylene carbonate (EC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), methyl acetate (MAC), and butyl acetate (BA) were mixed in a mass ratio of 4:2:3:3:2 to obtain a mixed solvent as a non-aqueous organic solvent, and additives and auxiliary agents were added to obtain a mixed solution. The mixed solution was sealed and packaged and placed in a quick freezer (-4°C) for 2 hours, then taken out and placed in a glove box filled with nitrogen (O 2 <1ppm,H 2 O<1ppm), slowly add lithium hexafluorophosphate (LiPF 6 ), and then the electrolyte is prepared after being evenly mixed;

[0032] (4) The positive electrode sheet, negative electrode sheet and separator are laminated to form a lithium-ion battery with a thickness of 4.7 mm, a width of 55 mm and a length of 60 mm. The battery is vacuum-baked at 75°C for 10 h and the electrolyte is injected. After standing for 24 h, the battery is charged to 4.4 V at a constant current of 0.1 C (180 mA), and then charged at a constant voltage of 4.4 V until the current drops to 0.05 C (90 mA); then discharged to 3.0 V at 0.2 C (180 mA), and the charge and discharge are repeated twice. Finally, the battery is charged to 3.8 V at 0.2 C (180 mA) to obtain a lithium-ion battery.

[0033] The formulations of the electrolytes of Examples 1 to 16 and Comparative Examples 1 to 6 are shown in Table 1, wherein the preparation processes of the electrolytes, positive electrode sheets, negative electrode sheets, and lithium-ion batteries of Examples 2 to 16 and Comparative Examples 1 to 6 are the same as those of Example 1.

[0034] Table 1 Compositions of the electrolytes of the embodiments and comparative examples

[0035]

[0036] The lithium ion batteries prepared in Examples 1 to 16 and Comparative Examples 1 to 6 were subjected to high temperature storage performance test, high temperature cycle performance test, room temperature cycle performance test, and low temperature performance test under the following conditions. The results are shown in Table 2.

[0037] High temperature storage performance test :

[0038] At room temperature (25°C), the lithium-ion battery was charged and discharged at 0.5C / 0.5C (the battery discharge capacity was recorded as C 0 ), the upper limit voltage is 4.4V, then the battery is charged to 4.4V under 0.5C constant current and constant voltage conditions, and the battery thickness is measured (the thickness is recorded as D 0 ); Place the battery in a 60°C oven for 30 days, take it out and measure the battery thickness (the thickness is recorded as D 1 ) ; Place the battery in a 25°C environment and discharge it at 0.5C (the discharge capacity is recorded as C 1 ); continue to charge and discharge the lithium-ion battery at 0.5C / 0.5C at room temperature (25°C) (the battery discharge capacity is recorded as C 2 ), with an upper voltage of 4.4 V, calculate the capacity retention rate, capacity recovery rate and thickness expansion rate.

[0039] Capacity retention rate = (C 1 / C 0 )*100%

[0040] Capacity recovery rate = (C 2 / C 0 )*100%

[0041] Thickness expansion rate = (D 1 / D 0 )*100%

[0042] Normal temperature cycle performance test :

[0043] At room temperature (25°C), the lithium-ion battery is charged and discharged at 1.0C / 1.0C (the battery discharge capacity is C 0 ), the upper limit voltage is 4.4V, and then 1.0C / 1.0C charging and discharging is performed at room temperature for 500 cycles (the battery discharge capacity is C 1 ), calculate the capacity retention rate.

[0044] Capacity retention rate = (C 1 / C 0 )*100%

[0045] High temperature cycle test :

[0046] Under high temperature (45°C), the lithium-ion battery is charged and discharged at 1.0C / 1.0C (the battery discharge capacity is C 0 ), the upper limit voltage is 4.4V, and then 1.0C / 1.0C charging and discharging is performed at room temperature for 400 cycles (the battery discharge capacity is C 1), calculate the capacity retention rate.

[0047] Capacity retention rate = (C 1 / C 0 )*100%

[0048] Low temperature performance test :

[0049] At room temperature (25°C), the lithium-ion battery is charged and discharged at 0.5C / 0.5 (the battery cut-off voltage is 3.0V and the discharge capacity is C 0 ), the upper limit voltage is 4.4V (cut-off current 0.05C). Then the battery is fully charged to 4.4V (cut-off current 0.05C) at 0.5C at room temperature (25℃), and then the battery is transferred to -20℃ and left for 4 hours, and discharged to 3.0V at 0.5C, with a discharge capacity of C 1 , calculate the capacity retention rate.

[0050] Capacity retention rate = (C 1 / C 0 )*100%

[0051] The acid values ​​of the electrolytes of the lithium ion batteries prepared in Examples 1 to 6 and Comparative Examples 1, 5 and 6 before and after high temperature cycling were tested under the following conditions. The results are shown in Table 3.

[0052] Acid value test of electrolyte:

[0053] Refer to SJ / T 11723-2018 Determination of free acid in electrolyte for lithium-ion batteries 4.5.1. After the potentiometric titrator is calibrated, accurately weigh 10.00g of electrolyte sample, add it to 50mL of anhydrous ethanol, titrate with 0.01mol / L weak organic base, record the titration volume, and the instrument automatically calculates the free acid content (in terms of HF) in the electrolyte.

[0054] Table 2 Lithium-ion battery performance test results

[0055]

[0056] Table 3 Acid value test results of electrolyte before and after high temperature cycle

[0057]

[0058] It can be seen from Table 3 that, compared with Comparative Example 1 and Comparative Example 1 and Comparative Example 6, the electrolytes of Examples 1 to 6 have relatively lower acid values ​​after high-temperature cycling, which indicates that compound B reacts with lithium hexafluorophosphate at high voltage and high temperature to produce HF; while compound A can hinder the forward reaction of lithium hexafluorophosphate to produce acid, and the chemical equilibrium moves toward lithium hexafluorophosphate, and the acid value of the electrolyte is greatly reduced. Therefore, compound A can significantly alleviate the increase of the acid value in the later stage of the battery cycle and effectively inhibit the decomposition of the SEI interface.

[0059] As shown in Tables 2 to 3, compared with Comparative Examples 1 and Comparative Examples 5 to 6, the lithium ion batteries of Examples 1 to 6 have better high and low temperature performance. This is because the electrolyte of the present invention includes compound A shown in structural formula 1 and compound B shown in structural formula II, wherein compound B reacts with lithium hexafluorophosphate at high voltage and high temperature to produce HF, destroying the stability of the battery interface and causing the battery performance to deteriorate, while compound A can hinder the forward reaction of lithium hexafluorophosphate to produce acid, and the chemical equilibrium moves toward the direction of lithium hexafluorophosphate, and the acid value of the electrolyte is greatly reduced, so compound A can significantly alleviate the increase of the acid value in the later stage of the battery cycle, and effectively inhibit the decomposition of the SEI interface. In addition, compound A and compound B can form a composite interface layer at the interface of the electrode electrolyte, and the composite interface layer has better lithium ion transmission characteristics, is not easy to shrink at low temperatures, can maintain the lithium ion transmission channel at low temperatures, and improves the low temperature performance of the lithium ion battery; at the same time, the composite interface contains sulfur and phosphorus interfaces, so that the high temperature stability of the electrolyte is better. In summary, the compounds A and B of the present invention can produce a synergistic effect, significantly alleviate the increase of the acid value in the later stage of the battery cycle, and effectively inhibit the decomposition of the SEI interface; they can also form a sulfur- and phosphorus-containing composite interface, improve the low-temperature transmission characteristics of lithium ions and the high-temperature stability of the electrolyte, so the electrolyte of the present invention can make the lithium-ion battery have better high and low temperature performance.

[0060] By comparing Example 8 with Examples 10 to 13, it can be seen that adding auxiliary agents on the basis of the additives of the present invention can further improve the high temperature storage performance, high temperature cycle performance, low temperature performance of the lithium ion battery, and the lithium ion cycle performance is better and the expansion rate is lower.

[0061] By comparing Examples 14 to 16 with Examples 10 to 11, it can be seen that when VC / FEC mixed additives are used in the electrolyte, the high temperature performance and low temperature performance of the lithium ion battery are greatly improved, and the expansion rate is further improved.

[0062] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. An electrolyte comprising a lithium salt, a non-aqueous organic solvent and an additive, wherein the lithium salt comprises lithium hexafluorophosphate, characterized in that: The additive comprises compound A shown in structural formula 1 and compound B shown in structural formula II, Wherein R1-R4 are each independently selected from hydrogen, alkyl, alkenyl, alkynyl; R5-R6 are each independently selected from halogen, alkyl, halogen-substituted alkyl.

2. The electrolyte according to claim 1, characterized in that R1-R4 are each independently selected from hydrogen, C1-C6 alkyl, C2-C6 alkenyl, C2-C6 alkynyl; R5-R6 are each independently selected from halogen, C1-C6 alkyl, halogen-substituted C1-C6 alkyl.

3. The electrolyte according to claim 1, characterized in that The compound A is selected from at least one of compounds A1 to A3:

4. The electrolyte according to claim 1, characterized in that The compound B is selected from at least one of compounds B1 to B4:

5. The electrolyte according to claim 1, characterized in that The mass percentage of the compound A in the electrolyte is 0.1-5.0%; the mass percentage of the compound B in the electrolyte is 0.1-10.0%.

6. The electrolyte according to claim 1, characterized in that The lithium salt also includes at least one of lithium perchlorate, lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), lithium methane sulfonate, lithium trifluoromethyl sulfonate, lithium fluorosulfonate, lithium bis(oxalatoborate), lithium difluorooxalatoborate, lithium difluorophosphate, lithium difluorobis(oxalatophosphate), lithium bis(fluorosulfonyl imide), lithium diphosphate and lithium lower aliphatic carboxylate.

7. The electrolyte according to claim 1, characterized in that The non-aqueous organic solvent is at least one of carbonate, carboxylate and ether compounds.

8. The electrolyte according to claim 1, characterized in that It also includes an auxiliary agent, which is selected from vinylene carbonate, vinylene carbonate, fluoroethylene carbonate, vinyl sulfite, 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, vinyl sulfate, succinic anhydride, maleic anhydride, 2-methylmaleic anhydride, methyl carbonate-2-propynyl ester, tetravinylsilane, triallyl isocyanurate, hexamethylene diisocyanate, o-phenanthroline, p-phenylene diisocyanate, 2, At least one of 4-toluene diisocyanate, N-phenylbis(trifluoromethanesulfonyl)imide, vinyl bissulfate, phenyl methanesulfonate, vinyl bissulfate, bis-spiro-propylene sulfate, hydroquinone difluorosulfonate, triallyl phosphate, tripropargyl phosphate, 2,4-butane sultone, isocyanoethyl methacrylate, methylene disulfonate, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, and tris(vinyldimethylsilyl)phosphate.

9. A lithium ion battery comprising a positive electrode and a negative electrode, characterized in that: Also includes the electrolyte according to any one of claims 1 to 8.

10. The lithium ion battery according to claim 9, characterized in that The active material of the positive electrode includes olivine-structured lithium-containing phosphate, lithium transition metal oxide and their respective modified compounds.

Citation Information

Patent Citations

  • Non-aqueous electrolyte containing fluorophosphamide salt and lithium ion battery

    CN111786020A

  • Non-aqueous electrolyte and lithium ion battery thereof

    CN114899484A

  • Difluoro cyclic sulfuric acid and boric acid lithium salt, electrolyte containing difluoro cyclic sulfuric acid and boric acid lithium salt and lithium ion battery

    CN117510528A

  • Non-aqueous electrolyte and lithium ion battery

    CN118472377A

  • An electric motor for Electro Hydraulic Actuator

    KR102705931B1